Venous thromboembolism - Chęciński, Paweł; Synowiec, Tomasz; Chęcińska, Zuzanna (Przewodnik Lekarza/Guide for GPs, 2006)
Venous thromboembolism (VTE) is one of the most important problems of contemporary medicine. It is connected with the fact, that this disease is common and in the case of the adverse effect of deep vein thrombosis, can lead to pulmonary embolism, a serious complication, which is a life-threatening event. Knowledge of pathophysiology, symptoms, additional investigations and appropriate treatment of venous thromboembolism, could significantly reduce the risk of death from this disease.